2015
DOI: 10.1093/ije/dyv142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MVA85A vaccine on tuberculosis challenge in animals: systematic review

Abstract: Background: The existing Bacillus Calmette–Guérin (BCG) vaccination provides partial protection against tuberculosis (TB). The modified vaccinia ankara virus-expressing antigen 85A (MVA85A) aims to boost BCG immunity. We evaluated the animal evidence supporting the testing of MVA85A in humans.Methods: Our protocol included in vivo preclinical studies of the MVA85A booster with BCG compared with BCG alone, followed by a TB challenge. We used standard methods for systematic review of animal studies, and summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…This was also the case for low level laser therapy for wound healing; after a SR of human studies found that the treatment was ineffective in humans [22], the authors systematically reviewed the animal studies [23] and concluded that they had not provided unequivocal evidence to substantiate the decision to conduct clinical trials. Similar conclusions were drawn in the cases of fluid resuscitation for bleeding trauma patients [24][25][26], endothelin for chronic heart failure [27,28] and more recently, a booster vaccine (MVA85A) intended to confer extra protection against tuberculosis [29,30]. In all these cases, it would be reasonable to conclude that conducting prospective SRs of the animal studies might have prevented expensive and unnecessary or risky clinical trials from proceeding; indeed this is often called for following the failure of a clinical trial, or the halting of a clinical trial that turns out to be dangerous [31].…”
Section: What Can Retrospective Srs Of Animal Studies Tell Us About Tsupporting
confidence: 57%
“…This was also the case for low level laser therapy for wound healing; after a SR of human studies found that the treatment was ineffective in humans [22], the authors systematically reviewed the animal studies [23] and concluded that they had not provided unequivocal evidence to substantiate the decision to conduct clinical trials. Similar conclusions were drawn in the cases of fluid resuscitation for bleeding trauma patients [24][25][26], endothelin for chronic heart failure [27,28] and more recently, a booster vaccine (MVA85A) intended to confer extra protection against tuberculosis [29,30]. In all these cases, it would be reasonable to conclude that conducting prospective SRs of the animal studies might have prevented expensive and unnecessary or risky clinical trials from proceeding; indeed this is often called for following the failure of a clinical trial, or the halting of a clinical trial that turns out to be dangerous [31].…”
Section: What Can Retrospective Srs Of Animal Studies Tell Us About Tsupporting
confidence: 57%
“…Despite potent immunogenicity of the Ag85a, a new vaccine based on this antigen was not promising. MVA85A, a modified vaccinia Ankara, expressing Ag85a, which initial research regarding this vaccine showed high levels of induction of longlasting cellular immunity in combination with the BCG vaccine, however, further results in clinical trials in 2015 were disappointing (14,(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that new TB vaccines that are compared to BCG should be interpreted cautiously with reference to a specific BCG formulation and not presumed to generalize to all BCGs [13]. In addition, testing the new concepts of vaccines in relevant animal models such as NHP, should be key before advancing into expensive clinical trials of efficacy [74,75]. Something that has been questioned in the MVA85A efficacy study [38] was that the efficacy experiments in NHP, which showed lack of efficacy by the tested clinical route and dose of administration [76,77].…”
Section: Target Population For a New Tb Vaccinementioning
confidence: 99%